“DEAR EMMA…”. GENRE OVERLAPPING AND REGISTER VARIATION IN THE ENGLISH AND ITALIAN VERSION OF SERGIO MARCHIONNE’S LETTER TO CONFINDUSTRIA - Manzella, Pietro (Comparative Legilinguistics, 2020)
Abstract: The aim of this paper is to examine whether genre overlapping and register variation have implications on the translation outcome. To this end, the English and the Italian version of the letter sent by Sergio Marchionne to the President of Confindustria – Italy’s most important employers’ organisation – will be analysed. The decision to investigate Marchionne’s statement is based on the fact that this is a letter disseminated in the form of a press release, which also contains highly-technical terminology pertaining to Employment Relations (ER) discourse. Consequently, a number of issues might arise when deciding which strategy should be used in terms of genre analysis and register when translating specialised texts.